Enhanced Ionic Accessibility of Flexible MXene Electrodes Produced by Natural Sedimentation - Sun, Ning; Guan, Zhaoruxin; Zhu, Qizhen; Anasori, Babak; Gogotsi, Yury; Xu, Bin (Nano-Micro Letters, 2020)
MXene nanosheets have been used for preparing highly flexible integrated electrodes due to their two-dimensional (2D) morphology, flexibility, high conductivity, and abundant functional groups. However, restacking of 2D nanosheets inhibits the ion transport in MXene electrodes, limiting their thickness, rate performance, and energy storage capacity. Here, we employed a natural sedimentation method instead of the conventional vacuum-assisted filtration to prepare flexible Ti3C2Tx MXene films with enlarged interlayer spacing, which facilitates the access of the lithium ions to the interlayers and thus leads to a greatly enhanced electrochemical performance. The naturally sedimented flexible film shows a double lithium storage capacity compared to the conventional vacuum-filtered MXene film, along with improved rate performance and excellent cycle stability. Highlights: 1 A simple, but effective strategy is proposed to prepare Ti3C2Tx MXene films by natural sedimentation method. 2 The enlarged interlayer spacing of the prepared films facilitates the accessibility of the lithium ions between the interlayers and thus leads to a greatly enhanced electrochemical performance. 3 The naturally sedimented MXene film shows a double lithium storage capacity compared to the conventional vacuum-filtered MXene film, along with improved rate performance and excellent cycle stability.